Oxidative Cleavage of Enamides with Hypervalent Iodine(III)/TMSN3 under an Air Atmosphere - Liu, Ge; Li, Yan; Sheng, Jie; Wang, Xi-Sheng (Synthesis, 2017)
An oxidative cleavage of C–C double bonds of enamides promoted by hypervalent iodine(III)/TMSN3 under an air atmosphere is developed. This reaction provides a new approach to construct various cyanobenzamides, which offers further synthetic potential for the preparation of industrial and pharmaceutical nitrogen- and oxygen-containing molecules, and exhibits good functional group tolerance, broad substrate scope and mild conditions.
Keywords: oxidative cleavage; enamides; hypervalent iodine(III); TMSN3; air atmosphere